Exploring tablets for undergraduate schoolwork - Chung, Yoona (Kansas State University, 2014)
Electronic reading (e-reading) device has been available for decades and there are many studies that have been published based on those devices. However with continuously changing tablet marketplace, there is a lack of studies looking at current devices. In order to understand the effect of tablets on undergraduate students, we conducted a consumer study to: 1) Determine the most beneficial tablet size for college students in their academic pursuits and 2) Determine the necessary types of support from academic libraries for college students conducting schoolwork using a tablet. An initial focus group study guided a consumer survey of 121 undergraduate students. The focus group study identified reading and note taking as key academic activities for tablet users. The participants were also interested in receiving quick help from the library and using electronic journal articles available from the library. A consumer survey took place at a university campus a month later. Each survey respondent answered a set of questionnaires using both large and small tablets of either Android or iOS operating system. The survey data showed that overall, larger tablet was preferred for academic use. Tablet size was not an important factor in reading or note taking (P ≥ 0.05) but perceived portability of a tablet size increased preference for that tablet size (P = 0.0078). In addition, the library’s instant messaging feature was found to be equally successful in both full and mobile website when viewed on a tablet (P ≥ 0.05). Many students who use HTML only or both HTML and PDF formats to view electronic journal articles when on a computer switched to PDF only when on a tablet. Our findings can assist tablet manufacturers in making a suitable tablet targeted for higher education uses. This study can also guide academic libraries in improving accessibility to resource for a growing number of undergraduate tablet users.
Keywords: Tablet; Consumer study; Academic library; Education, Technology (0710); Library Science (0399)